Fundamentals of graphic design-essential tools for effective visual science communication - Karen J. Murchie; Dylan Diomede (Canadian Science Publishing, 2020)
Guidance on improving the visual aspects of science communication range from "recipe"-style instructions to hyper-focused aspects of data visualization. Currently lacking in the peer-reviewed literature is a primer in graphic design tailored to a high-level overview of basic design principles and associated jargon related to layout, imagery, typeface, and colour. We illustrate why these aspects are important to effective communication. Further, we provide considerations on when to solicit professional assistance and what to expect when working with graphic designers. Having the fundamental principles of good design in your toolbox facilitates the production of effective visual communication related to your research and fruitful scientist-designer collaborations.